Acceptable macronutrient distribution ranges and hypertension. (18th August 2015) - Lee, Eunna; Choi, Jaekyung; Ahn, Ahleum; Oh, Eunjung; Kweon, Hyukjung; Cho, Dongyung
Abstract: Acceptable macronutrient distribution ranges (AMDRs) for carbohydrate, fat, and protein have been set by considering epidemiological evidences that suggest consumption within these ranges plays a role in reducing risk of chronic diseases. Little evidence has been presented on the relationship between the intake outside the AMDR for macronutrient and hypertension. Therefore, this study was performed to examine the association between the intake outside the AMDR and hypertension in Korean adults. This study was based on data obtained from the fifth Korean National Health and Nutrition Examination Survey. The AMDR for carbohydrate is 55–70%, for fat is 15–25%, and for protein is 7–20% of the energy intake for adults. The subjects who did not meet the AMDRs for carbohydrate, fat and protein were considered to be the non-AMDR group. The odds ratio of the non-AMDR group was 1.25 (95% CI, 1.02–1.53) in the hypertensive subjects without anti-hypertensive medication and 1.25 (95% CI, 1.06–1.48) in the hypertensive subjects with anti-hypertensive medication after adjustment for age, sex, current smoking, heavy drinking, physical inactivity, obesity, diabetes mellitus, dyslipidemia, total energy intake, high sodium intake, and vitamin D deficiency. The intake outside the AMDR was significantly associated with hypertension in Korean adults. The AMDR might be useful nutritional requirement for dietary management of hypertension. In the future, these findings need to be verified through prospective population-based studies.